CHRONIC LYMPHOCYTIC LEUKEMIA ARISING IN A PATIENT WITH HODGKIN LYMPHOMA TREATED WITH PERIPHERAL BLOOD STEM CELL TRANSPLANTATION - Case report - Trajkova, Sanja; Pivkova Veljanovska, Aleksandra; Popova Labachevska, Marija; Ivanovski, Martin; Krstevska Balkanov, Svetlana; Ridova, Nevenka; Stojanovska, Simona; Panovska Stavridis, Irina (Macedonian Association of Anatomists, 2022)
Post-transplant lymphoproliferative disorders (PTLDs) are lymphoid or plasmacytic proliferations. These disorders develop as a consequence of immunosuppression in a recipient of a solid organ, bone marrow or stem cell allograft. The development of PTLDs is usually associated with Epstein-Barr virus (EBV) and the disorder is also termed EBV-associated lymphoproliferative disorder (LPD). The development of PTLD is a rare complication in autologous bone marrow/peripheral blood stem cell transplantation. In this study, we will present a case of LPD which developed following an autologous peripheral blood stem cell transplantation for relapsing Hodgkin's lymphoma
Keywords: CLL; COVID-19; post-transplant lymphoproliferative disorders